Massive acquisition of conjugative and mobilizable integrated elements fuels Faecalibacterium plasticity and hints at their adaptation to the gut - Gérard Guédon; Florence Charron-Bourgoin; Thomas Lacroix; Toufik Hamadouche; Nicolas Soler; Badreddine Douzi; Hélène Chiapello; Nathalie Leblond-Bourget (Scientific Reports)
Abstract Faecalibacterium is one of the most abundant bacteria of the human gut microbiota of healthy adults and is recognized to have positive effects on health. Here, we precisely and comprehensively analyzed the conjugative mobilome of four complete Faecalibacterium genomes. Despite lacking any plasmid, these bacteria harbor a vast arsenal of 130 elements, including 17 integrative and conjugative elements (ICEs) and 83 integrative and mobilizable elements (IMEs), collectively comprising 14–23% of the genome. Genome comparison of two strains isolated from the same fecal sample (Faecalibacterium and Roseburia strains) revealed almost identical elements indicating that transfer of ICEs and IMEs shape gut microbiome. ICEs and IMEs from Faecalibacterium encode many and diverse predicted functions such as defense and stress response (phages, multidrug, antibiotics, oxidative stress, biliar salts, antimicrobial peptides), nutrient import and metabolisms (Fe3+, carbohydrates) and riboflavin synthesis. This hints at their important role in the survival and adaptation of Faecalibacterium strains to the gut ecosystem. A rapid survey of 29 additional Faecalibacterium genomes uncovered many putative ICEs and IMEs, reinforcing their role in the rapid and massive evolution of Faecalibacterium genomes.